The Study Of Consumer Protection In The Mystery Box Sale And Purchase Agreement On Shopee Marketplace Viewed From Indonesian Law - Afiq, Muhammad Adib; Najib Imanullah, Moch. (International Journal of Educational Research & Social Sciences, 2023)
This study analyzes the Consumer Protection Study on the Mystery Box Sale and Purchase Agreement on the Shopee Marketplace viewed from Indonesian Law. This research is a normative legal research using secondary data sources through library research. The results of the study show that the Mystery Box Sale and Purchase Agreement in the Shopee marketplace violates the provisions of Article 1320 of the Civil Code regarding the element of "halal causes", and there are no specific rules regarding the protection of consumers who carry out electronic transactions, so that the rules regarding consumer protection are still referring to the Law of the Republic of Indonesia number 8 of 1999 concerning Consumer Protection. In this research, the case will be discussed in a comprehensive manner regarding the concept of a Mystery Box Sale and Purchase agreement and how to protect consumers regarding mystery box buying and selling transactions on the Shopee marketplace. This research is projected as a basis for studying in analyzing similar cases regarding Consumer Protection in Mystery Box Sale and Purchase Agreements on the Shopee Marketplace viewed from Indonesian Law Rules later in the future. The limitation of this research lies in the study using library data sources. In the future, it is hoped that similar research could use this research as a basic reference in conducting research that can obtain concrete data in the field. Thus, it can provide more factual outcomes according to the conditions that occur.